Filtration losses in oilwell cement contaminated by pseudo oil base muds (2010)
Contamination of oilfield cement slurries by drilling fluids is one of the causes of cement job failures and it results in expensive remedial actions. While the general adverse effects of Pseudo Oil Base Mud (POBM) contamination of cement slurries are known, little has been published on the actual effects of POBM on specific slurry properties. The effect of POBM on the filtration losses in oil well cement slurries was investigated. POBM contaminated slurries at varying contamination volumes up to 40% at intervals of 5% were prepared. The filtration losses were determined using standard American Petroleum Institute (API) procedures. The results show that while API fluid losses increased with time, it decreased with increasing POBM contamination in cement slurries.